WORK STRESS, RISK-TAKING PROPENSITY, AND RESILIENCE AS DETERMINANTS OF PSYCHOLOGICAL WELLBEING IN THE POLICE FORCE - Adekanmbi, Foluso Philip; Ukpere, Wilfred Isioma (Annals of Spiru Haret University. Economic Series, 2022)
This study evaluates the impacts of work stress, risk-taking propensity, and resilience on psychological wellbeing in Nigeria’s Police Force. Its sample was extracted from four (4) police stations in Ibadan, Oyo State of Nigeria. They are the Iyaganku, Eleyele, Orita Challenge, and Iwo Road testing ground police stations. This study has adopted a cross-sectional survey method, where the current scholar randomly distributed the study’s questionnaires. Nonetheless, from the 350 questionnaires floated, 319 were suitable for study and analyzed using Statistical Packages for Social Sciences (SPSS version 27). The present study conducted standard and hierarchical multiple regression analysis in testing the stated hypotheses and concludes that work stress and risk-taking propensity significantly reduce psychological wellbeing. In contrast, resilience increases it in Nigeria’s Police Force. It further settles that work stress, risk-taking propensity, and resilience significantly and jointly determine psychological wellbeing. Work stress, however, determines more significantly the psychological wellbeing of police officers than risk-taking propensity, resilience, and their combination matrix. Consequently, this paper advocates the need to reinforce stress management training among police officers to promote healthy lifestyles and improve psychological wellbeing. Also, Nigeria’s Police college should incorporate risk-taking concepts on the job to help them exhibit better risk-taking behaviors and maintain improved psychological wellbeing. Moreover, Nigeria’s Police Force should adopt strategies for promoting resilience levels, raising police officers’ positive emotions to recover from their adverse experiences. Besides, there is a severe need for psychological interventions to prepare police officers for the hurdles ahead. So, it is required that government make provisions for a salary increase, incentives, organizational support programs, and initiatives that can strengthen the coping styles of police officers for better psychological health and wellbeing.